Using Different Physical Activity Measurements in Eight European Countries. Results of the European Physical Activity Surveillance System (EUPASS) Time Series Survey. - Rütten, Alfred; Ziemainz, Heiko; Schena, Frederico; Stahl, Timo; Stiggelbout, M; Vanden Auweele, Y; Vuillemin, Anne; Welshman, J (Public Health Nutrition, 2003)
Objectives: The European Physical Activity Surveillance System (EUPASS) research project compared several physical activity (PA) measures (including the International Physical Activity Questionnaire (IPAQ)) in a time series survey in eight countries of the European Union. The present paper describes first results provided by the different instruments regarding PA participation, frequency and duration, both at the European and national levels. The purpose of the present study is to explore and compare the specific quality and usefulness of different indicators rather than to provide valid and reliable prevalence data. Thus, the main focus is on discussion of the methodological implications of the results presented. Methods: A time series survey based on computer-aided telephone interviewing (CATI) was carried out in eight European countries over a six-month period. The study provided for about 100 realised interviews per month in each country (i.e. ∼600 per country). Descriptive statistical analysis was used to: (1) report IPAQ results on vigorous, moderate and light PA and sitting, as well as on the overall measure of calories expenditure (MET min-1), in the different countries; (2) compare these results with national PA indicators tested in EUPASS; and (3) compare IPAQ results with other European studies. Results: First, the scores for the different PA categories as well as for the overall measure of calories expenditure provided by the IPAQ appeared rather high compared with previous studies and public health recommendations. Second, the different PA measurements used in EUPASS provided completely different results. For example, national indicators used in Germany and The Netherlands to date neither corresponded in absolute values (e.g. means of PA or sitting) nor correlated with the IPAQ in any significant way. Third, comparing EU countries, the ranking for vigorous, moderate and light activities by use of the IPAQ differed from that of other European studies. For example, in the present analysis, German respondents generally showed higher scores for PA than the Finns and the Dutch, while, in contrast, findings from other studies ranked Finland before The Netherlands and Germany. Conclusions: The present analysis highlights some methodological implications of the IPAQ instrument. Among other things, differences in overall scores for PA as well as in the ranking of nations between the present results using IPAQ and other measures and studies may partly be due to the concepts of PA behind the measurements. Further analysis should investigate if the range of PA-related categories provided by the IPAQ is fully appropriate to measure all relevant daily activities; it may also consider the public health implications of mixing up different contexts of PA (e.g. work, leisure-time, transportation) in the IPAQ short versio
UnivIS-Import:2015-03-09:Pub.2003.phil.dps.iss.lsw.usingd
Keywords: International comparison; Measurement; Physical activity; Public health